2017
DOI: 10.1080/24748668.2017.1390723
|View full text |Cite
|
Sign up to set email alerts
|

The influence of floaters on players’ tactical behaviour in small-sided and conditioned soccer games

Abstract: 6This study examined players' tactical behaviours based on core tactical principles during 7 small-sided and conditioned games (SSCG) with and without floaters on the sidelines. 8 A total of 24,068 tactical actions performed by 168 Under-17 academy soccer players 9 were assessed using the System of Tactical Assessment in Soccer (FUT-SAT; Teoldo, 12 revealed that players showed different tactical behaviours depending on the SSCG 13 format and playing phase. In "Floaters off" SSCG, players more frequently perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 33 publications
6
53
0
4
Order By: Relevance
“…In general, these results were already expected, since we decreased task difficulty level by introducing three floaters in the game. Through specific performance indicators used in the present study, such as Passes and Ball touches, we observed that the LD-SSCG stimulates teams to keep ball possession, since these games enabled a greater number of passes and ball touches, corroborating with Padilha, Guilherme, Serra-Olivares, Roca, and Teoldo (2017). Other research has also found that the presence of inside or outside floaters stimulates teams to keep ball possession (Castellano, Silva, Usabiaga, & Barreira, 2016).…”
Section: Differences Between the Training Tasks With Different Difficsupporting
confidence: 78%
“…In general, these results were already expected, since we decreased task difficulty level by introducing three floaters in the game. Through specific performance indicators used in the present study, such as Passes and Ball touches, we observed that the LD-SSCG stimulates teams to keep ball possession, since these games enabled a greater number of passes and ball touches, corroborating with Padilha, Guilherme, Serra-Olivares, Roca, and Teoldo (2017). Other research has also found that the presence of inside or outside floaters stimulates teams to keep ball possession (Castellano, Silva, Usabiaga, & Barreira, 2016).…”
Section: Differences Between the Training Tasks With Different Difficsupporting
confidence: 78%
“…A total of 32 soccer players, 16 U-13 (VO 2 max estimated: 46.01 ± 2.73 ml/kg/min; height: 156.2 ± 9.40 cm; weight: 46.5 ± 8.37 kg) and 16 U-14 (VO 2 max: 47.91 ± 2.43 ml/kg/min; height: 166.8 ± 7.34 cm; weight: 55.9 ± 8.52 kg) participated in this study. Goalkeepers were not evaluated, as previously reported in the literature on ssG [9,10]. the players belonged to a team that participated in national competitions and presented no injuries at the moment of the study.…”
Section: Participantsmentioning
confidence: 99%
“…Notwithstanding, the literature shows that players' technical performance is influenced by ssG type [1]. In this article, we focused on the influence of floaters during ssG on both physical [8] and tactical aspects [6,9], providing a more integrated perspective of the use of ssG training. It is suggested that the inclusion of these additional players (always to the offensive team, inside or outside the pitch) promotes higher ball circulation, since the usual absence of a defender assigned to this player allows safe passing possibilities [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, training exercises should stimulate perception-action cycles [7], as characteristic of the competition context, through manipulating practice areas (e.g., field width and length) and game objectives and rules (task conditions) [8,9]. Applying small-sided games (SSGs) allows to coordinate players at different moments of the game and promote tactical principles that guide the playing style of the team [10,11].…”
Section: Introductionmentioning
confidence: 99%